Développement du jeu jeter la carte comme support d’apprentissage des nombres en français - Fingki Widia Sari Silalahi; Zulherman (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2024)
This study aims to develop ‘Les Nombres’ material based on a card game in French for students. This research is a type of research and development (R&D). This study uses Sugiyono’s steps with modifications and five steps used, namely: (1) identification of potentials and problems, a needs analysis was carried out using a questionnaire addressed to class X SMA Swasta Budi Agung, and interviews with teachers. This step was carried out to determine the learning conditions in this school and to determine the need to develop card-tossing games. (2) Data collection and the identification of existing barriers were also carried out. Data was collected from needs analysis questionnaires, interviews with teachers, and documentary studies; (3) Product design, the comic strips are designed using the Canva application; (4) Product validation, the product is a modified comic medium and is validated by experts. The validation process is carried out by two experts, the material experts and the media experts; and (5) product advice, after obtaining expert advice, the product design is validated. The product is revised or improved based on the results of the assessment provided by media and material experts to achieve a decent standard. This study aims to develop media support for the French card-throwing game for pupils. The material used is ‘Nombres’. Data analysis with the percentage of descriptive quantitative approach. The results of the research and development of this card-throwing game were declared feasible from a material point of view with a feasibility level of 80% and from a media point of view with a feasibility level of 90%. Based on the results of the study, it can be concluded that the material and the card-throwing games developed can be applied to teaching French numbers to pupils.